2000
DOI: 10.1055/s-2000-8616
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Pharmacokinetics of Natural Volatile Terpenes in Animals and Humans

Abstract: Herbal medicinal products containing natural volatiles are used in the treatment of gastrointestinal diseases, pain, colds and bronchitis. Many pharmacological studies report a wide variety of in vitro effects, with anti-inflammatory and antimicrobial activities investigated most frequently. In comparison, relatively few studies on the bioavailability and pharmacokinetics have been carried out. Thus, the relevance of the in vitro activity to the therapeutic effects found in individual studies or documented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
0
19

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(168 citation statements)
references
References 20 publications
4
145
0
19
Order By: Relevance
“…The excess terpene may have failed to be absorbed through the digestive tract, or may have been readily eliminated. This low accumulation is consistent with the high clearance values observed by Kohlert et al (2000), who determined the average half-life of a variety of monoterpenes and oxygen-containing derivatives to be about one hour.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The excess terpene may have failed to be absorbed through the digestive tract, or may have been readily eliminated. This low accumulation is consistent with the high clearance values observed by Kohlert et al (2000), who determined the average half-life of a variety of monoterpenes and oxygen-containing derivatives to be about one hour.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless all this information has been provided by pharmacological studies in non-ruminant species (Kohlert et al, 2000), by studies on terpene elimination in milk (Viallon et al, 2000;Fernandez et al, 2003), or by studies in which terpene ingestion was not controlled (Cornu et al, 2001a,b;Priolo et al, 2004). Specific difficulties hinder the study of terpene fingerprints in ruminant meat products.…”
Section: Introductionmentioning
confidence: 99%
“…Kohlert et al [38] found that there is little risk in accumulation of these compounds as they likely have a short half-life (hours) in the human body and are quickly eliminated. It was concluded that most of the essential oil constituents are metabolized into carbon dioxide by the body or excreted in conjugated form by the kidneys, with a small fraction of inhaled terpenoids released from the lungs during exhalation [38].…”
Section: Studies In Human Subjectsmentioning
confidence: 99%
“…The site of intestinal absorption of essential oils in monogastrics might influence its effect on the animal. Kohlert et al (2000) observed that the absorption of thymol in humans occurs in the upper intestine. In pigs, essential oils can be absorbed in the proximal portion of the intestine, and therefore, the antimicrobial activity in the distal portion of the intestine is limited (Muhl and Liebert, 2007).…”
Section: Resultsmentioning
confidence: 99%